Survei Sarana dan Prasarana Cabang Olahraga Taekwondo di Kota Ternate - Mahatma Raison Pribadi (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the facilities and infrastructure of taekwondo sports in Ternate City, so that the advantages and disadvantages of facilities and infrastructure in each taekwondo training ground (Dojang) in Ternate City can be known. This research is a quantitative descriptive research with survey method. All training places (Dojang) in Ternate City, while the sample in this study amounted to 5 training places (Dojang) using observation and documentation data collection techniques. The results of the research on the survey of facilities and infrastructure show that: 1 Dojang gets category 4 (good) with an average value of 262.7, 2 Dojang which gets category 3 and 2 (moderate and less) with an average value of 175.8 and 162.1 and 2 Dojang which gets category 1 (very poor) with an average value of 58.3 and 54.02. This means that the facilities and infrastructure for taekwondo sports in Ternate City are categorised as lacking.